Water for Agricuture. Construction of three types of infrastructure to collect water for agricultural production: water harvesting, hand-dug wells, and sinks to collect - Maradiaga Corea, Marco Antonio; López Fonseca, Ernesto Antonio; Palma Zepeda, Osman; Arévalo Castillo, Alfonso Alejandro (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the Environment (PROGRESA.) One of PROGRESA’s main goals was increasing crop and livestock production, and one way of helping to raise this production was improving water availability, especially during dry periods. Thus, part of the support provided to the beneficiary families through the rural water program was smallscale rural infrastructure works, which allowed the improvement of agricultural productivity applying Good Agricultural Practices (GAPs) and Good Animal Husbandry Practices (GAHPs). Similarly, PROGRESA improved the water supply for human consumption with rural mini-aqueducts, although the main purpose of this document is sharing the experience constructing three types of infrastructure to collect water for production: water-harvesting works (ponds and reservoirs), hand-dug wells, and sinks to collect spring water.